(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Hernioplasty is a surgical procedure designed to restore the anatomical integrity of muscles and tissues and to strengthen structures that are prone to protrusion of internal organs beyond their natural position through defects in muscular structures. It is often used in the treatment of hernias, which is the protrusion of internal organs through weak areas in muscles or connective tissues, usually caused by defects in the abdominal wall.